2020
DOI: 10.1007/s12328-020-01276-4
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis and atezolizumab therapy: an atypical case

Abstract: Immune checkpoint inhibitors such as anti-CTLA-4 (cytotoxic T-lymphocyte-associated protein 4), anti-PD-1 (programmed cell death protein 1), and PD-L1 (programmed cell death protein-ligand 1) are emerging drugs that have radically changed treatment and prognosis of different types of tumors. However, despite their considerable benefits, immune checkpoint inhibitors are associated with numerous side effects involving several organs. Gastrointestinal toxicities represent some of these most common adverse events.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…They found that most of the patients need steroid, while a minority of them required IFX or vedolizumab, regardless of whether in the initial or recurrent episode. Our analysis showed that 25% (8/32) of patients (36,41,43,46,48,54,57) had recurrent ICI-mediated colitis without ICI retreatment, which received subsequent therapy involving probiotics, antidiarrheal drugs, antiviral drugs, steroid, and immunosuppressants. Four cases with CIC finally did not improve or deteriorate after the second treatment (36,41,48,54).…”
Section: Rechallenge and Recurrencementioning
confidence: 87%
See 1 more Smart Citation
“…They found that most of the patients need steroid, while a minority of them required IFX or vedolizumab, regardless of whether in the initial or recurrent episode. Our analysis showed that 25% (8/32) of patients (36,41,43,46,48,54,57) had recurrent ICI-mediated colitis without ICI retreatment, which received subsequent therapy involving probiotics, antidiarrheal drugs, antiviral drugs, steroid, and immunosuppressants. Four cases with CIC finally did not improve or deteriorate after the second treatment (36,41,48,54).…”
Section: Rechallenge and Recurrencementioning
confidence: 87%
“…However, the atypical feature of microscopic colitis has also been reported, like crypt abscesses and neutrophilic cryptitis of active IBD (178). Gallo et al (41) reported a patient with lung cancer who received atezolizumab presented collagenous colitis along with acute neutrophilic inflammation. Besides, Choi et al (179) showed that patients with microscopic colitis induced by ICIs would have higher hospitalization rates and more aggressive course of disease and need more treatments like steroids and/or immunosuppressants than those without exposure to ICIs.…”
Section: Pathological Featuresmentioning
confidence: 99%
“…One case of an infliximab refractory colitis was also described in a patient treated with nivolumab; in follow up, the patient developed bowel perforation that required total colectomy with terminal ileostomy; the patient eventually died from sepsis 35 days after the colectomy was performed [36]. When speaking about ICI induced colitis, although the usual histologic and endoscopic findings resemble that of the IBD, there are also reports of some unusual cases such as collagenous colitis after pembrolizumab and atezolizumab therapy [37,38]. ePub ahead of printing A case of pseudomembranous colitis in a 57-year-old patient with hepatocellular carcinoma was reported, contributing to the constellation of different manifestations and endoscopic findings that can occur with anti PD-1 therapy [39].…”
Section: Discussionmentioning
confidence: 99%
“…While cases of severe colitis associated with anti CTLA-3 therapy are rather frequent, severe cases after anti PD-1 therapy are scarcely reported, with an incidence of only 0.4 % [36]. Some unusual cases of colitis were also described, such as collagenous [37,38], pseudomembranous [39], granulomatous [40], microscopic colitis [41] or even inflammatory bowel diseases (IBD) [42][43][44] due to different types of ICI.…”
Section: Gastrointestinal Tract Toxicitymentioning
confidence: 99%
“…Immune-related adverse events, including colitis, are well-documented side effects of treatment with immune checkpoint inhibitors and some case reports have documented cases of MC following immune checkpoint inhibitor treatment. This suggests that immunomodulatory molecules play a key role in maintaining gut homeostasis (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%